German Forecast in Winter 2024: No Recovery in Sight - Jens Boysen-Hogrefe; Dominik Groll; Timo Hoffmann; Nils Jannsen; Stefan Kooths; Christian Schröder; Nils Sonnenberg (Kiel Institute for the World Economy (IfW Kiel), 2024)
The German economy is stuck in stagnation. There are no signs of a significant economic recovery. Instead, there are increasing signs that the economic weakness is primarily structural rather than cyclical, which means there is little room for improvement in economic activity in the short term. There is also a risk of additional headwinds in the coming year. If the new US administration follows through on its protectionist announcements, as assumed in this forecast, this will be a further drag on exports. Exports have already failed to keep pace with world trade recently, as companies have become less competitive. The provisional budget management, which is necessary due to the end of the coalition and will remain in place well into next year, could also slow economic output, although the effects are likely to be small. Against this backdrop, we have lowered our forecast and expect GDP to stagnate next year (fall forecast: +0.5%), following a decline of 0.2% in the current year (fall forecast: -0.1%). In 2026, economic output is expected to grow by 0.9% (fall: 1.1%), whereby almost 0.3 percentage points are attributed to the additional number of working days. The economic weakness is leaving its mark on the labor market. The unemployment rate will rise from 5.7% in 2023 to 6% this year and 6.3% next year. After a noticeable increase this year, real disposable household income will barely grow in the next two years. As a result, private consumption will not gain much momentum either. Gross fixed capital formation will gradually bottom out as financing conditions improve somewhat. The budget deficit is expected to be around 2 percent of GDP over the next two years, down from 2.3 percent this year.
Keywords: 330; Germany; Financial Markets; Growth; Labor Market; Monetary Policy; Economic Policy in German; Business Cycle Germany